2019
DOI: 10.1111/ejn.14418
|View full text |Cite
|
Sign up to set email alerts
|

Incentive and dopamine sensitization produced by intermittent but not long access cocaine self‐administration

Abstract: The temporal pattern of drug use (pharmacokinetics) has a profound effect on the ability of self‐administered cocaine to produce addiction‐like behavior in rodents, and to change the brain. To further address this issue, we compared the effects of long access (LgA) cocaine self‐administration, which is widely used to model the transition to addiction, with intermittent access (IntA), which is thought to better reflect the pattern of drug use in humans, on the ability of a single, self‐administered injection of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 87 publications
2
42
1
Order By: Relevance
“…While rats trained to self-administer cocaine using LgA procedures consume more drug, rats trained using IntA show greater motivation to work for cocaine compared to rats in LgA or ShA training (Zimmer et al, 2012). Rats also show greater cue-induced drug-seeking behavior following IntA training compared to LgA or ShA (Kawa et al, 2016, 2019). IntA results in greater dopamine concentrations within the NAc core following a single infusion of cocaine compared to LgA training, and dopamine levels correlated with several measures of motivation for cocaine (Kawa et al, 2019).…”
Section: Contingent Models Of Addiction-related Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…While rats trained to self-administer cocaine using LgA procedures consume more drug, rats trained using IntA show greater motivation to work for cocaine compared to rats in LgA or ShA training (Zimmer et al, 2012). Rats also show greater cue-induced drug-seeking behavior following IntA training compared to LgA or ShA (Kawa et al, 2016, 2019). IntA results in greater dopamine concentrations within the NAc core following a single infusion of cocaine compared to LgA training, and dopamine levels correlated with several measures of motivation for cocaine (Kawa et al, 2019).…”
Section: Contingent Models Of Addiction-related Behaviorsmentioning
confidence: 99%
“…Rats also show greater cue-induced drug-seeking behavior following IntA training compared to LgA or ShA (Kawa et al, 2016, 2019). IntA results in greater dopamine concentrations within the NAc core following a single infusion of cocaine compared to LgA training, and dopamine levels correlated with several measures of motivation for cocaine (Kawa et al, 2019). IntA training, but not LgA or ShA, using psychostimulants also results in sensitization of NAc dopamine transports (Calipari et al, 2013, 2014).…”
Section: Contingent Models Of Addiction-related Behaviorsmentioning
confidence: 99%
“…As few as 3 IntA cocaine sessions sensitize cocaine's effects at the DAT, and after one week of abstinence, both cocaine potency and stimulated DA release are increased even further [54]. Using in vivo microdialysis in freely moving rats, it has recently been reported that IntA, but not LgA, sensitizes cocaine-induced overflow in the NAc core [51]. Furthermore, IntA cocaine experience enhances amphetamine and methylphenidate's effects at the DAT [29], and IntA methylphenidate experience produces sensitization-related effects similar to those produced by cocaine [55].…”
Section: Box 1: Does Lga Experience Reliably Produce Tolerance To Cocmentioning
confidence: 99%
“…Different patterns of drug exposure produce diverse effects on mesolimbic dopamine function and addiction-related behavior (e.g., refs. [ 14 25 ]). Decreased sensitivity (i.e., tolerance) is typically reported after relatively continuous patterns of opioid administration, whereas increased sensitivity (i.e., sensitization) is commonly observed after more intermittent patterns of opioid exposure [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%